(untitled) (KIUT Publication, 2025)
This article analyzes the potential of increasing the share of electricity from renewable energy sources and utilizing biomass resources in the decarbonization of the energy sector to mitigate the effects of climate change. It is substantiated that biogas technologies can meet 15–20 percent of the country’s energy demand.